Measurement of Some X-ray Quality Control Parameters to Optimize Diagnostic Reference Levels - Claus, Thiago Victorino; Cassol, Luísa Vargas; Favarin, Nataly Nogueira; Nogueira, Laura Pizarro Trojahn; Gomes, Tobias Soares; Schwarz, Stefanie Camile; Torres, Herculis Rolins; Baumhardt, Tadeu (Science and Technology: Developments and Applications Vol. 9, 2025)
Background: The characterization of the X-ray beam (kVp, mAs, filtration, focus-skin distance), the patient's anthropometric characteristics (thickness, beam projection), and the anatomical region of interest allows an estimation of skin entrance dose (Ka,e). Currently, the comparison of values obtained with Diagnostic Reference Levels (DRLs) makes it possible to identify opportunities to reduce the dose of ionizing radiation, contributing to safe and efficient radiological practice. Aims: This experimental study aimed to quantify the entrance surface air kerma (Ka,e) of X-ray beams in radiographic examinations, comparing the obtained values with national and international Diagnostic Reference Levels (DRLs). Methodology: The research was conducted at the Department of Medical Physics and Radiology of the Franciscan University (UFN) between June 2023 and August 2024. The X-ray beam evaluation used a dosimetric set to measure the Air Kerma Rate (KAIR) and determine the X-ray tube output. A phantom without water and another filled with water were employed to calculate the backscatter factor (BSF) and estimate Ka,e for the main radiographic examinations. Before the start of the study, quality control (QC) procedures for the radiographic equipment were carried out according to current guidelines and regulations to ensure accurate and reliable results. Results: The results identified anatomical regions with the highest radiation exposure, reinforcing the need for optimization. It was observed that, although Ka,e values were within national limits, they exceeded the reference values of the United Kingdom and Japan in the skull, abdomen, and lumbar spine regions. For example, for the AP projection skull radiographic exam, the estimated Ka,e value was 4.30 mGy, whereas in Japan, the corresponding DRL is 3.0 mGy. Similarly, for the chest in the PA projection, the estimated Ka,e value is 0.17 mGy, while in the United Kingdom, the corresponding DRL is 0.3 mGy. This difference highlights the importance of periodically updating DRLs in accordance with international recommendations and technological advancements. Dose optimization requires continuous assessment of image quality, proper selection of technical parameters, and implementation of specific dose protocols. Ongoing training for radiology professionals is essential to ensure the correct application of imaging techniques and reduce patient exposure to ionizing radiation. Conclusion: The results obtained demonstrate the need for adjustments in imaging acquisition protocols, as the Ka,e values found in this study. The methodology adopted in this study can contribute to the ongoing education of radiology professionals, promoting the correct application of imaging techniques and reducing patient exposure to ionizing radiation. Furthermore, this study emphasizes the need for a multidisciplinary approach to dose optimization, combined with quality assurance programs and continuous professional training, ensuring greater patient safety and high-quality diagnostic imaging.